Poly(dodecyl methacrylate) as solvent of paraﬃns for phase change materials and thermally reversible light scattering films - Puig, Julieta (2013)
Paraffins are typical organic phase change materials (PCM) used for latent heat storage. For practical applications they must be encapsulated to prevent leakage or agglomeration during fusion. In this study it is shown that eicosane (C20H42 = C20) in the melted state could be dissolved in the hydrophobic domains of poly(dodecyl methacrylate) (PDMA) up to concentrations of 30 wt %, avoiding the need of encapsulation. For a 30 wt % solution, the heat of phase change was close to 69 J/g, a reasonable value for its use as a PCM. The fully converted solution remained transparent at 80 °C with no evidence of phase separation but became opaque by cooling as a consequence of paraffin crystallization. Heating above the melting temperature regenerated a transparent material. A high contrast ratio and abrupt transition between opaque and transparent states was observed for the 30 wt % blends, with a transparent state at 35 °C and an opaque state at 23 °C. This behavior was completely reproducible during consecutive heating/cooling cycles, indicating the possible use of this material as a thermally reversible light scattering (TRLS) film.